2021
DOI: 10.1302/0301-620x.103b3.bjj-2020-1308.r1
|View full text |Cite
|
Sign up to set email alerts
|

Complications, mobility, and quality of life in ankle sarcoma patients

Abstract: Aims The aims of the study were to analyze differences in surgical and oncological outcomes, as well as quality of life (QoL) and function in patients with ankle sarcomas undergoing three forms of surgical treatment, minor or major limb salvage surgery (LSS), or amputation. Methods A total of 69 patients with ankle sarcomas, treated between 1981 and 2017 at two tumour centres, were retrospectively reviewed (mean age at surgery: 46.3 years (SD 22.0); 31 females (45%)). Among these 69 patients 25 were analyzed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In this study, as in previous reports, 20% of patients with malignant or intermediate malignancy had died from diseases, and 53% had undergone amputation. Usually, to fulfill the oncological goal of treatment, wide resection and reconstruction are warranted; however, when complete resection of the tumor is difficult or there is a high risk of local recurrence after resection, amputation of the foot or the leg is recommended [26]. Malignant bone tumors of the forefoot should be treated locally with amputation at a level appropriate for the proximal extension of the tumor [27]; accordingly, in three of our cases, amputations at the metatarsal and metatarsophalangeal disarticulation were performed in the first surgery, and neither of 4 The change rate of comparison between bone and soft tissue lesions using the JSSF scale from preoperative to postoperative in each subcategory (a) and total scale (b).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as in previous reports, 20% of patients with malignant or intermediate malignancy had died from diseases, and 53% had undergone amputation. Usually, to fulfill the oncological goal of treatment, wide resection and reconstruction are warranted; however, when complete resection of the tumor is difficult or there is a high risk of local recurrence after resection, amputation of the foot or the leg is recommended [26]. Malignant bone tumors of the forefoot should be treated locally with amputation at a level appropriate for the proximal extension of the tumor [27]; accordingly, in three of our cases, amputations at the metatarsal and metatarsophalangeal disarticulation were performed in the first surgery, and neither of 4 The change rate of comparison between bone and soft tissue lesions using the JSSF scale from preoperative to postoperative in each subcategory (a) and total scale (b).…”
Section: Discussionmentioning
confidence: 99%
“…Several small samples or single-center clinical cohort studies have shown that LSS had a better prognosis than amputation among patients with EBST sarcomas ( 13 , 29 ). In addition to the postoperative survival rate, clinicians are increasingly concerned about the higher recurrence rate and complications caused by limb salvage procedures, as these are associated with a poorer prognosis ( 9 , 10 , 30 ). Some studies have reported no significant difference in the incidence of local recurrence of sarcoma among patients who underwent LSS and amputation ( 8 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the conventional wisdom that radical surgery reduces recurrence rate and complications ( 8 ), limb salvage surgery (LSS) has become increasingly attractive to orthopedists and patients with EBST sarcomas because of the minimal impairment to physical appearance and function. However, there remained a question as to whether LSS has a detrimental effect on the survival of sarcoma patients ( 9 , 10 ). In a comparative study encompassing 1,220 patients with osteosarcoma treated with neoadjuvant chemotherapy, 36% and 20% of patients developed local recurrence following limb salvage with intralesional margins and marginal margins, respectively, but no events were observed among patients receiving amputation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intercalary resection (when possible) or ankle arthrodesis provided the most reliable functional outcome over osteoarticular reconstructions. In looking specifically at ankle sarcomas, Smolle et al found similar quality of life and activity between patients who underwent limb salvage and those who underwent amputation, and a higher risk of complications with limb salvage 14 . These data suggest that, in cases that require more than minor procedures for limb salvage, amputation provides equivalent outcomes and lower complications.…”
Section: Bone Tumorsmentioning
confidence: 99%